Combined experimental and numerical evaluation of the differences between convective and conductive thermal control on the performance of a lithium ion cell - Ardani,MI; Patel,Y; Siddiq,A; Offer,GJ; Martinez-Botas,RF (Energy, 2017)
Testing of lithium ion batteries is necessary in order to understand their performance, to parameterise and furthermore validate models to predict their behaviour. Tests of this nature are normally conducted in thermal/climate chambers which use forced air convection to distribute heat. However, as they control air temperature, and cannot easily adapt to the changing rate of heat generated within a cell, it is very difficult to maintain constant cell temperatures. This paper describes a novel conductive thermal management system which maintains cell temperature reliably whilst also minimising thermal gradients. We show the thermal gradient effect towards cell performance is pronounced below operating temperature of 25 °C at 2-C discharge under forced air convection. The predicted internal cell temperature can be up to 4 °C hotter than the surface temperature at 5 °C ambient condition and eventually causes layers to be discharge at different current rates. The new conductive method reduces external temperature deviations of the cell to within 1.5 °C, providing much more reliable data for parameterising a thermally discretised model. This method demonstrates the errors in estimating physiochemical paramet ers; notably diffusion coefficients, can be up to four times smaller as compared to parameterisation based on convective test data.